CONSUMER SEGMENTATION OF REFILLED DRINKING WATER IN PADANG - Awisal Fasyni; Mukhamad Najib; Kirbrandoko Kirbrandoko (Indonesian Journal of Business and Entrepreneurship (IJBE), 2015)
The purposes of this study were to analyze consumer segmentation of refilled drinking water based on their behavior and to recommend strategies for increased sales of Salju depot. The study was conducted using a survey of family and non-family consumers in Nanggalo, North Padang, West and East Padang. The respondent selection technique is using a convenience sampling, which is based on the availability of elements and easiness of obtaining these samples. The analysis used for segmentation is cluster analysis and CHAID. The results showed that there were five segments in family consumer and four segments in non-family consumer. Each family segment was different in terms of usage and consumption level, while non-family segments differ in terms of consumption duration and consumption level. Salju depot could aim market segments that provide benefits, specifically segments with high consumption levels both in family and nonfamily consumers, maintain the price and quality of the product and show the best performance in serving customers, set the open hours and optimize the messaging services.Keywords: refilled drinking water, segmentation, Padang, CHAIDABSTRAKPenelitian ini bertujuan menganalisis segmentasi konsumen air minum isi ulang berdasarkan perilakunya dan merekomendasikan strategi peningkatan penjualan bagi depot Salju. Penelitian dilakukan dengan metode survei terhadap konsumen keluarga dan konsumen nonkeluarga di Kecamatan Nanggalo, Kecamatan Padang Utara, Kecamatan Padang Barat dan Kecamatan Padang Timur Kota Padang. Teknik pemilihan responden menggunakan convenience sampling, yaitu berdasarkan ketersediaan elemen dan kemudahan mendapatkan sampel tersebut. Analisis yang digunakan untuk segmentasi adalah analisis cluster dan CHAID Hasil penelitian menunjukkan terdapat lima segmen konsumen keluarga dan empat segmen konsumen nonkeluarga. Masing-masing segmen keluarga berbeda dalam hal penggunaan dan tingkat konsumsi, sedangkan segmen nonkeluarga berbeda dalam hal lama konsumsi dan tingkat konsumsi. Salju dapat menyasar segmen yang dapat memberikan keuntungan yaitu segmen dengan tingkat konsumsi yang tinggi baik untuk keluarga maupun nonkeluarga, mempertahankan harga dan kualitas produk yang dihasilkan serta menampilkan performa terbaik dalam melayani konsumen dan menetapkan jam buka dan jam layanan pesan antar yang optimal. Kata kunci: air minum isi ulang, segmentasi, Padang, CHAID